2020
DOI: 10.14740/cr1084
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Characteristics of Subjects With COVID-19: A Case Series

Abstract: Although coronavirus disease 2019 manifests in most cases with respiratory symptoms, other presentations can occur. Direct damage to the cardiovascular system has been reported and recently, acute myocardial injury has been identified as a risk factor for mortality. Transthoracic echocardiography is a non-invasive tool that allows the detection of myocardial damage with validated markers (left ventricular ejection fraction and global longitudinal strain). Herein, we present the echocardiographic findings in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is unclear whether this finding was associated with SARS-CoV-2 infection, or represented actual bacterial endocarditis or the presence of thrombus. Other studies have reported the presence of tricuspid vegetations that disappeared in subsequent echocardiographic evaluation in patients with negative blood cultures [56]. The presence of valve vegetations was also described in autopsy findings for SARS-CoV patients [57].…”
Section: Other Echocardiographic Abnormalities In Covid-19mentioning
confidence: 83%
“…It is unclear whether this finding was associated with SARS-CoV-2 infection, or represented actual bacterial endocarditis or the presence of thrombus. Other studies have reported the presence of tricuspid vegetations that disappeared in subsequent echocardiographic evaluation in patients with negative blood cultures [56]. The presence of valve vegetations was also described in autopsy findings for SARS-CoV patients [57].…”
Section: Other Echocardiographic Abnormalities In Covid-19mentioning
confidence: 83%
“… 51 , 55 , 57 LV dysfunction, in the form of either wall motion abnormalities or reduced ejection fraction, has been reported in various studies. 7 , 18 , 53 57 , 64 The wall motion abnormalities in some patients were found to resemble stress-induced cardiomyopathy 7 , 54 , 57 , 58 , 61 , 64 , 66 Churchill et al reported resolution of LV dysfunction in 82% of patients who underwent a follow-up echocardiography after a median 14 days. 53 In the present study, LV diastolic dysfunction was a common echocardiographic finding, seen in 56% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although disease outcomes of COVID-19 are worsened by a pre-existing cardiovascular disease, the associated high burden of systemic inflammation is thought to be the main factor that predisposes to the development of subclinical disorders or even causes de novo cardiovascular damage 15 . Approximately 1 in 5 patients with COVID-19 experiences de novo myocardial injury, which may remain as a chronic consequence of the disease, 16 or worse, could be identified as a cause of mortality 17 . Beyond myocardial injury, an interesting recent study on 4 cases of COVID-19 found that 1 patient, with no prior history of heart disease, developed a vegetation in the tricuspid valve and severe tricuspid regurgitation 17 .…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…Approximately 1 in 5 patients with COVID-19 experiences de novo myocardial injury, which may remain as a chronic consequence of the disease, 16 or worse, could be identified as a cause of mortality 17 . Beyond myocardial injury, an interesting recent study on 4 cases of COVID-19 found that 1 patient, with no prior history of heart disease, developed a vegetation in the tricuspid valve and severe tricuspid regurgitation 17 . It was noted that patients infected with SARS-CoV have also developed endocarditis with vegetations in previous reports 18 …”
Section: Cardiovascular Complicationsmentioning
confidence: 99%